A novel, balloon-borne UV-Vis spectrometer for direct sun measurements of stratospheric bromine - Voss, Karolin; Holzbeck, Philip; Pfeilsticker, Klaus; Kleinschek, Ralph; Wetzel, Gerald; Fuentes Andrade, Blanca; Höpfner, Michael; Ungermann, Jörn; Sinnhuber, Björn-Martin; Butz, André (Atmospheric measurement techniques, 2024)
We report on a novel, medium-weight (∼ 25 kg) optical spectrometer coupled to an automated sun tracker for direct sun observations from azimuth-controlled balloon platforms weighing approximately 12 kg. It is designed to measure a suite of UV-Vis absorbing gases relevant in the context of stratospheric ozone depletion using the differential optical absorption spectroscopy (DOAS) method, i.e. O3, NO2, BrO, OClO, HONO, and IO. Here, we describe the design and major features of the instrument. Further, the instrument's performance during two stratospheric deployments from Esrange near Kiruna (Sweden) on 21 August 2021 and from Timmins (Ontario, Canada) on 23 August 2022 is discussed along with the first results concerning inferred mixing ratios of BrO above balloon float altitude. Using a photochemical correction for the partitioning of stratospheric bromine ([BrO]/[Bry]) obtained by chemical transport simulations, the inferred total stratospheric bromine load [Bry] amounts to (17.5 ± 2.2) ppt, with a purely statistical error amounting to 1.5 ppt in (5.5 ± 1.0)-year old air. The latter is inferred from simultaneous measurements of N2O by the GLORIA (Gimballed Limb Observer for Radiance Imaging of the Atmosphere) mid-IR instrument, resulting in a stratospheric entry of the investigated air mass in early 2017 ± 1 year.